2020
DOI: 10.1093/jrr/rraa059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gamma irradiation-induced mutations in Arabidopsis mutants deficient in non-homologous end joining

Abstract: To investigate the involvement of the non-homologous end joining (NHEJ) pathway in plant mutagenesis by ionizing radiation, we conducted a genome-wide characterization of the mutations induced by gamma rays in NHEJ-deficient Arabidopsis mutants (AtKu70−/− and AtLig4−/−). Although both mutants were more sensitive to gamma rays than the wild-type control, the AtKu70−/− mutant was slightly more sensitive than the AtLig4−/− mutant. Single-base substitutions (SBSs) were the predominant mutations in the wild-type co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The molecular mutation profile at the genome scale can also be used for selecting a proper mutagen for mutation breeding and gene function analysis. Re-sequencing analysis of progeny of mutagenized plant material has provided a new perspective aimed at characterizing the mutation molecular profile of various physical mutagens at the whole-genome scale in the last 10 years [ 31 , 33 , 36 , 40 , 41 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In earlier research, only one mutant line was sequenced since it was still costly to perform NGS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mutation profile at the genome scale can also be used for selecting a proper mutagen for mutation breeding and gene function analysis. Re-sequencing analysis of progeny of mutagenized plant material has provided a new perspective aimed at characterizing the mutation molecular profile of various physical mutagens at the whole-genome scale in the last 10 years [ 31 , 33 , 36 , 40 , 41 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In earlier research, only one mutant line was sequenced since it was still costly to perform NGS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ichida detected only 3.0 inversions from 110 M 2 rice lines derived from 150 Gy carbon-ion beam irradiation [ 64 ]. Only one inversion was detected in 19 M 2 individuals of NHEJ-deficient Arabidopsis thaliana mutants (AtKu70 −/− and AtLig4 −/− ) that were irradiated with gamma rays (100 Gy) [ 60 ]. In rice, Li detected four SVs in seven M 5 plants with visible mutated traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that the highly excessive number of heterozygous mutations resulted from purging homozygosity of mutations with recessive lethal effects, because the annotation analysis shows that high-impact mutations (i.e., loss-of-function gene mutations) accounted for only 7.7% of total mutations (Supplementary Table S2). Previous studies of the genetic consequences of acute/chronic radiation only during the vegetative stage showed that the heterozygous/homozygous ratio of mutations followed the Mendelian segregation ratio [e.g., 6, 12, 14, 40]. On the other hand, in this study, life-cycle chronic irradiation induced a greater number of heterogeneous mutations that should occur after gametogenesis, i.e., any reproductive stage from gamete formation to fertilization, zygote development, and then seed maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Plant lines and growth mutants used in this study: ku70 19,42 (Col-0, SALK_123144), ku70 19,32 (Ws), ku80 19 (SALK_016627), lig4 42 (SALK_044027), tdp2-1 (SALK _043413), teb-5 9,43 (SALK_018851), mre11-2 19,29 . Double mutants were created by crossing single mutants.…”
Section: Methodsmentioning
confidence: 99%